I Would Like to Be Truthful, But…: A Systemic Study of Academic Dishonesty From Conscientiousness, Performance Goal Orientation, Competition, and Peer Influence Perspectives - Dyah Ayu Kusumawardani Gunawan; Andrian Pramadi (ANIMA Indonesian Psychological Journal, 2018)
Academic dishonesty is any behavior in the learning process which violates the principles of justice and integrity, in order to get higher marks. The complexity of the phenomenon requires a systemic analysis which considers individual and contextual factors. This research used the incidental sampling survey method. The research subjects were 535 Faculty of Psychology students from the 2013 to 2016 classes of Universitas Surabaya. The research goal was to examine the role of individual factors, including conscientiousness and performance goal orientation, and also contextual factors, including competition and peer influence, regarding academic cheating. The research results showed that conscientiousness, performance goal orientation, competition, and peer influence together contributed to academic cheating in the amount of 11.6% (R = 0.340, p = .000). The analysis of each factor showed that there are three factors influencing academic cheating, these being conscientiousness (partial correlation = - .262, p = .000), competition (partial correlation = .129, p = .003), and peer influence (partial correlation = .189, p = .000). However, performance goal orientation did not play any role (partial correlation = .066, p = .128). This implied the existence of other factors, such as self-efficacy, academic achievement, and university regulations.